2020
DOI: 10.3389/fcell.2020.00709
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stellate Cells and Hepatocarcinogenesis

Abstract: Hepatic stellate cells (HSCs) are a significant component of the hepatocellular carcinoma (HCC) tumor microenvironment (TME). Activated HSCs transform into myofibroblastlike cells to promote fibrosis in response to liver injury or chronic inflammation, leading to cirrhosis and HCC. The hepatic TME is comprised of cellular components, including activated HSCs, tumor-associated macrophages, endothelial cells, immune cells, and non-cellular components, such as growth factors, proteolytic enzymes and their inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 179 publications
(254 reference statements)
0
78
0
Order By: Relevance
“…The activation of HSCs represents a pivotal moment in this picture. Indeed, activated HSCs can differentiate in a senescent profile, inducing the recruitment and the activation of immune cells from the bloodstream, including TAMs, as well as increasing the growth factor receptor signaling, in particular PDGF and TGF-β [ 195 ]. In line whit this, recent findings suggest the TGF-β ability to inhibit the activation and functions of Natural Killer (NK) cells by repressing the mammalian target of rapamycin (mTOR) pathway [ 196 ].…”
Section: The Immune Response In Hcc Developmentmentioning
confidence: 99%
“…The activation of HSCs represents a pivotal moment in this picture. Indeed, activated HSCs can differentiate in a senescent profile, inducing the recruitment and the activation of immune cells from the bloodstream, including TAMs, as well as increasing the growth factor receptor signaling, in particular PDGF and TGF-β [ 195 ]. In line whit this, recent findings suggest the TGF-β ability to inhibit the activation and functions of Natural Killer (NK) cells by repressing the mammalian target of rapamycin (mTOR) pathway [ 196 ].…”
Section: The Immune Response In Hcc Developmentmentioning
confidence: 99%
“…HSCs are resident perisinusoidal cells that contribute to diverse aspects of liver physiology, including hepatic organogenesis, regeneration, vitamin A storage, and wound healing (34). Under non-pathologic conditions, HSCs remain quiescent in the liver and are only activated in response to liver injury (35). In addition to serving as the primary source of ECM proteins, activated HSCs secrete a multitude of cytokines and growth factors that are required for fibrogenesis and promote HCC tumorigenesis (34)(35)(36)(37)(38)(39).…”
Section: Hepatic Stellate Cellsmentioning
confidence: 99%
“…However, it has been shown that activation of CAFs by TGF-β leads to dysregulated extracellular matrix (ECM) architecture and excess fibrosis, both of which favor tumor progression [104] . The clinical significance of TGF-β is that Produce growth factors such as EGF [68] Increase collagen production [85] Favor tumor encapsulation [86] Greater tumor cell proliferation Reduced overall survival [87] Promote hepatocarcinogenesis HSC Reduce lymphocyte infiltration of tumor [88] Shift monocytes towards immunosuppression [89] Inhibit lymphocyte infiltration in tumors [90] Enhance tumor angiogenesis [90] Increased hepatic fibrosis [91] Greater HCC recurrence [89] Reduced immune surveillance Sustains tumor metabolism TAM Release growth factors and cytokines Suppress immunity by recruiting Tregs [92] Larger tumor size [85] Reduced overall survival [93]…”
Section: Non-cellular Playersmentioning
confidence: 99%